The Role of Circulating Adiponectin and SNP276G>T at ADIPOQ Gene in BRCA-mutant Women - DANIELE, ANTONELLA (Cancer Genomics Proteomics, 2020)
Background: Environmental factors may influence the lifetime risk of cancer (penetrance) in women with a BRCA mutation. Materials and Methods: In 89 BRCA-mutant women, affected or unaffected by breast/ovarian cancer, we explored serum levels of adipokines and their relation with the polymorphism SNP276G>T as modulators of BRCA penetrance. Results: Affected women had significantly lower adiponectin than healthy women. Affected women with rs1501299 TT had significantly lower adiponectin and higher leptin than GT and GG genotypes. GT genotype was significantly associated with the disease status [odds ratio (OR)=3.24, 95% confidence interval (95% CI)=1.03-10.17]. Women in the lower tertile of serum adiponectin had a RR of BRCA-associated cancer of 2.80, 95% CI=1.1-7.1 (p for trend=0.03) compared with women in the higher tertile. Conclusion: In the SNP rs1501299 the T allele was significantly associated with lower serum levels of adiponectin in affected women, suggesting that the T allele might be related to cancer.